Profit power economics : a new competitive strategy for creating sustainable wealth - De Kuijper, Mia. (New York ; Oxford : Oxford University Press, 2009)
'Profit Power Economics' is a manual of competitive strategy & value-investing for the economic realities of the 21st century an age in which information costs are getting close to zero and everyone is connected. This book offers a new economic paradigm for our age-and the tools to make the most of it.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Strategic planning; Profit; Information technology -- Management